1 - The Alternative Genealogy of Civil Society and Its Implications for Africa: Notes for Further Research: DOI: 10.4314/ad.v29i4.22204 - Obadare, Ebenezer (Africa Development, 2004)
Despite its ubiquity in popular and academic discourses, consensus about the epistemological status of the idea of civil society remains elusive. In Africa, the literature is circumscribed by doubts about, first, its applicability; and second, the usefulness of civil society in explicating social processes on the continent. This has generated a conflictive, yet deeply illuminating, scholarship. The paper makes a modest contribution to the debate, first, by mapping the main contours of the existing intellectual divide, and second, critically complicating it by suggesting the emergence of an 'alternative genealogy' that seemingly renders the debate itself redundant. The 'alternative genealogy' seems to have emerged, partly out of the desire to respond to misgivings about the possibility of civil society in Africa, and partly to provide a description of civil society which, while not totally divorced from its original meaning(s), nevertheless strikes out in fresh directions, taking into cognisance the radical ways in which the notion of civil society is being used across non-Western societies in general. The paper concludes with an examination of the implications of this re-imagining of civil society for both theoretical analysis and practical engagement.